2013
DOI: 10.1021/ic400913f
|View full text |Cite
|
Sign up to set email alerts
|

Brilliant Photoluminescence and Triboluminescence from Ternary Complexes of DyIII and TbIII with 3-Phenyl-4-propanoyl-5-isoxazolonate and a Bidentate Phosphine Oxide Coligand

Abstract: Three new lanthanide heterocyclic β-diketonate complexes [Dy(PPI) 3 (EtOH) 2 ] (1), [Dy(PPI) 3 (DPEPO)] (2), and [Tb(PPI) 3 (DPEPO)] (3) [where HPPI = 3-phenyl-4-p r o p a n o y l -5 -i s o x a z o l o n e a n d D P E P O = b i s ( 2 -(diphenylphosphino)phenyl)ether oxide] have been synthesized and fully characterized. Single-crystal X-ray diffraction analyses reveal that these complexes are mononuclear and that the central Ln III ion is coordinated to eight oxygen atoms that are provided by three bidentate β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(65 citation statements)
references
References 63 publications
7
55
0
2
Order By: Relevance
“…9) which overlaps with the excitation spectrum of the MOF, indicating the energy transfer from ligand (fluorescein) to Sm 3þ . Thus the coordination and sensitization of Sm 3þ ions to fluorescein molecules are confirmed [19]. The emission spectra of the synthesized MOF at different excitation wavelengths are shown in Fig.…”
Section: Photoluminescence Propertiessupporting
confidence: 54%
“…9) which overlaps with the excitation spectrum of the MOF, indicating the energy transfer from ligand (fluorescein) to Sm 3þ . Thus the coordination and sensitization of Sm 3þ ions to fluorescein molecules are confirmed [19]. The emission spectra of the synthesized MOF at different excitation wavelengths are shown in Fig.…”
Section: Photoluminescence Propertiessupporting
confidence: 54%
“…First we observe that while the addition of the DPEPO ligand to the Dy:Y(acac) 3 system improves the material's fluorescence lifetimes, the addition of the phen ligand decreases the performance of the Dy:Y(acac) 3 system. This observation is consistent with previous observations on the influence of the phen ligand on Dy(acac) 3 [32] and on other lanthanide-doped complexes [23,47] as well as the influence of DPEPO on other lanthanide-doped complexes [33,34,37,48]. Additionally, we find that when we substitute hfa for acac in Dy:Y(acac) 3 (DPEPO) the fluorescence lifetime drastically decreases, despite the H-F substitution of the acac ligand.…”
Section: A Ranking the Complexes Performancesupporting
confidence: 93%
“…This implies that the DPEPO ligand improves the performance of the Dy complex, while the phen ligand decreases the performance. These results are consistent with previous studies involving these ligands where phen was observed to decrease the performance of ternary complexes [23,32,47], while DPEPO improved the performance [33,34,37,48]. Phen's negative effect is attributed to its relatively low triplet level [32,47], while DPEPO's enhancing effect is attributed to its compact rigid structure [34].…”
Section: B Effect Of Ligand Choicesupporting
confidence: 91%
“…[14,15] Molecular crystalsc omposed of lanthanide complexesa nd coordination polymers have recently been studied for effective triboluminescence. [16][17][18][19][20] While there have been extensived iscussions on the origin of triboluminescence from molecular crystals, somes tudies have indicatedacontribution of the piezoelectric effect upon breaking non-centrosymmetric bulk crystals. [21] The Eu III coordination polymers with triangular spacers in Figure 1a,b are expected to provide close packed structures and effective crystal cracking under mechanical stress.…”
Section: Introductionmentioning
confidence: 99%